Probability of occurrence of the turbulent flow structures in transitional pipe flows - Krauß, Jens; Ertunc, Özgür; Ostwald, Christina; Lienhart, Hermann; Delgado, Antonio (Notes on Numerical Fluid Mechanics and Multidisciplinary Design. New Results in Numerical and Experimental Fluid Mechanics VIII, 2013)
During laminar-to-turbulent transition in low Reynolds number (Re) pipe flows, two main types of turbulent flow structures occur: puff and slug. Puff structures can be initiated by inducing short-time, large amplitude localized disturbances in the pipe. They are equilibrium structures, i.e. they do not grow. Furthermore, they dissipate at random as they travel along the pipe. Therefore, they represent an incomplete relaminarization process. However, lifetimes of puffs diverge or attain very high values at some critical Re. At Reynolds numbers higher than this critical value, disturbances evolves from puff to slug through multiple splitting. In other words, the flow structures start to grow and fill the space. During this evolution, many types of structures occur. This evolution is associated with the onset of turbulence. In the present work, detailed experiments on the probability of occurrence and propagation speed of puffs, splitting puffs and slugs were conducted. During the investigations, fully developed laminar pipe flow was disturbed by an iris diaphragm with a pre-defined amplitude and duration. Different types structures, such as single puff, splitting puff and slugs, are classified and the probability of their occurrence at the end of pipes with different lengths are evaluated. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-20:Pub.2013.tech.ITC.stmmec.probab_8